DESAIN ULANG LEMARI MIXING E POXY PADA PT EXCELITAS TECHNOLOGIES BATAM - Gunawan, Ade; Sirait, Ganda (LPPM Universitas Putera Batam, 2023)
PT Excelitas is a company located in the batamindo area that produces light detectors or often called sensors. However, even though the excelitas company has made efforts to run an adequate work area, there are still work areas that need to be improved, such as the epoxy mixing cabinet work area, which has no shelves to tidy up tools and machines and no safety cover on the machine so that operators who carry out the epoxy mixing process can be exposed to epoxy splashes, so that it can cause inconvenience to operators who carry out production activities in the area because they can be exposed to epoxy splashes during the epoxy mixing process. To determine the results of the redesign that will be applied, this study uses the NIDA method, namely Need, determining the needs of the epoxy mixing cabinet, idea, idea to solve the problem of the epoxy mixing cabinet, decision to make a decision on the design of the epoxy mixing cabinet, and action, namely making a prototype design of the epoxy mixing cabinet by redesigning the safety cover and storage rack of the epoxy mixing cabinet. With the redesign of the safety cover on the epoxy mixing machine, operators who operate epoxy mixing are no longer exposed to epoxy splashes that come out during the epoxy mixing process and storage shelves that function to store tools during the epoxy mixing process.